Deceived bilateral filter for improving the automatic cell segmentation and tracking in the NF-kB pathway without nuclear staining - Mora Rodríguez, Rodrigo Antonio (2014)
artículo -- Universidad de Costa Rica, Escuela de Ingeniería Eléctrica. 2014